Determination of Prulifloxacin Using the Eu(III) as the Fluorescence Probe by Spectrofluorimetry - Zhang, Xiaojie; Xie, Yong; Zhuo, Xin; Shi, Hongwei; Xu, Jigui (Asian Journal of Chemistry, 2012)
The fluorescence of the prulifloxacin (PUFX)-Eu(III) system was investigated. Experiments indicated that the fluorescence intensity of Eu(III) could be greatly decreased by prulifloxacin. Accordingly, a sensitive spectrofluorimetric method for the determination of prulifloxacin was established,and its optimum detection conditions were also studied. Using Eu(III) as a fluorescence probe, which was excited at 241 nm, the decreased fluorescence intensity at 485 nm of the system (DF) showed a good linear relationship with the concentration of prulifloxacin within the range 5.0 × 10-8-1.00 × 10-5 mol L-1 and the regression equation was DF = -6.54 + 3.53 × 10-6 C(mol L-1) (n = 7). The correlation coefficient was 0.9989 and the detection limit (3 s/k) for the determination of prulifloxacin was 2.8 × 10-8 mol L-1. This method is simple, practical and relatively free interference from coexisting substances and can be successfully applied to determination of prulifloxacin.